Characteristics, Behavior, and Environmental Conditions Residence of Leptospirosis Patients in the District of Probolinggo - Fransisca Putri Intan Damalia; Atik Choirul Hidajah; Agus Ardiyansyah (State Islamic University of Sunan Ampel, 2021)
Leptospirosis is a zoonotic disease caused by Leptospira sp. and carried by rats as the main source of transmission through its urine. Risk factors for the sufferer are the condition and activity of daily individuals. Probolinggo Regency became one of the regencies/cities in East Java that had been infected by Leptospirosis and as of 20 January 2020 the case amounted to 4 and 2 of which died. This research aims to illustrate the characteristics, behaviors, and environmental conditions of the Leptospirosis in Probolinggo Regency. The research was conducted by describing four cases of Leptospirosis found in Probolinggo Regency from 1 – 20 January 2020. The cases found are depicted according to characteristic variables, behaviors, and environmental conditions. Data analysis is done in a descriptive, namely describing the distribution and presentation of each variable. Data is presented in a table or narrative form. The results showed that 75% of the patients of Leptospirosis are male-gender with an age range of 45-59 years old. Work of some sufferer (50%) is a risky job, namely farmers and builders. No sufferers use gloves during contact with puddle, the use of footwear to the yard and the habit of washing hands and feet after the activity is only done by some sufferers (50%). Almost all sufferers (75%) using well water as a source of clean water. 50% of sufferers do not have sewers. Most sufferers (75%) have pets or livestock and be aware of the presence of rats in the house. Bins owned by most sufferers (75%) is a type of open trash can. Half of the number of sufferers residing in flood prone areas. Therefore, it takes a disciplined attitude in the implementation of clean and healthy life during activities to prevent the occurrence of Leptospirosis.